Efektivitas Remediasi Kognitif terhadap Perbaikan Fungsi Kognitif pada Penderita Skizofrenia Rawat Inap di Rumah Sakit Jiwa A di Yogyakarta - Weni Susilo Rini; M. Noor Rochman Hadjam (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2016)
The aim of this reasearch to evaluate the effectiveness of cognitive remediationtherapy in improving cognitive function of schizophrenia inpatient. This research was aquasi experimental with untreated control group design with dependent pretest andposttest. Fourteen schizophrenic inpatients were assigned to either a cognitiveremediation group (n=7) or a control group (n=7). Cognitive dysfunctions were assessedusing validated Indonesian version of Cognitive Assessment Interview (CAI). Theintervention consisted of 12 sessions in 3 weeks, and was conducted in groups. ResultCognitive training group showed significant improvements in attention(effect size 0.65),working memory (effect size 0.68) and processing speed (effect size 0.61)after theintervention compared to the control group, but no significant improvement in globalcognitive function. Conclusion the research suggests that cognitive remediation is noteffective to improve global cognitive function and effective to improve attention, workingmemory and processing speed in hospitalized schizophrenic patients.